Collaborating to embed academic literacies and personal support in first year discipline subjects - Chanock, Kate; Horton, Craig; Reedman, Mark; Stephenson, Bret (Journal of University Teaching and Learning Practice, 2012)
This article discusses a Design for Learning project in the Faculty of Humanities and Social Sciences, where academic and personal support for students was interwoven in their first semester. Staff of the Academic Language and Learning Unit (ALLU) worked with discipline staff to develop their students’ capabilities across a range of disciplines, while the Faculty’s First Year Coordinator organised dedicated tutors to identify and support students who struggled to engage with their first semester’s work. ALLU staff, consulting with subject coordinators, designed extra tutorials focussing on the subjects’ readings for four weeks, and working towards the first marked assignment. Using ALLU’s design, subject tutors showed students what is characteristic of thinking at university; how that is embodied in the structures and styles of academic texts; and how sources are used. Feedback from students, tutors, and coordinators was mainly favourable, and a comparison of students’ entrance scores and first semester marks with those of previous cohorts found that As and Bs rose in most subject groups, while Ds and Fails decreased, despite lower entrance scores overall.The article situates this initiative within the movement towards “embedding” development of students’ academic literacies into their disciplines’ curricula. It looks at the educational advantages of this method, as well as some difficulties of acceptance, ownership, and organisation. It focusses, in particular, on the benefits of involving ALLU staff, with their expertise in Applied Linguistics, in designing activities to focus both students and subject lecturers on the particular discourses used in their discipline subjects.